Cloning: Paglikha ng Kopya, Pagkopya ng Nilikha - de Castro, Leonardo (Philippine Social Sciences Review; Social Sciences and Health Issue, Ed. Carmen C. Jimenez, 2010)
The success achieved by Scottish scientists in the cloning of adult mammals has made human cloning a distinct possibility. Can the cloning of a human being be seen as the copying of a person? Can it be viewed as the production of a mere copy? Society now finds itself having to address these as well as other questions with unsettling ethical implications. The asexual nature of the process involved in this novel reproductive technique could render male participation superfluous, necessitating a review of our notion of fatherhood. It also turns the concept of motherhood into a paradox by allowing more than one genetic mother to emerge, making womb-only-motherhood a necessity. It forces us to rethink traditional concepts of personhood by recalling the mythical image of a “putok sa buho”. The potential for genetic manipulation of offspring as part of the cloning process provides a reason to test human beings for undesirable traits with a view to “genetic correction”. But genetic testing also opens up opportunities for eugenic selection. When human beings screen or manage the birth of “lives not worth living”, they maybe engaging in a misguided attempt to play God. On the other hand, they may merely be expressing their human creativity. What is upon us are not purely scientific dilemmas. We are confronted with a revolutionary opportunity to re-invent humanity. This is a responsibility which no one can afford to shirk.
Keywords: cloning